MODELING CLOTHING ORDER SIZE GROUPING AT RIZKY CONVECTION USING THE K-MEANS METHOD - Rahmadani, Putri; Hutahaean, Jeperson; Santoso, Santoso (Universitas Royal, 2025)
Abstract: Rizky Convection Business is a sportswear production company based on Jalan Elang Lestari Kisaran. Every day they receive orders from schools and agencies that need sportswear. However, Rizky Convection often faces challenges, especially in managing raw material inventory, allocating production time and processing orders that come in large quantities. For this reason, order data needs to be grouped to make it easier for employees to work on it. The data that will be processed in this study is order data from 2022-2024. One way to do this is to apply data mining techniques, one of which is the K-Means Clustering method. The purpose of this study is to model the use of K-Means Clustering to improve production management and procurement of raw materials for fabrics at Rizky Convection. K-Means Clustering is the grouping of a number of data into clusters (groups) so that each cluster will contain data that is as similar as possible. The results of K-Means Clustering grouping with 3 clusters, namely cluster 1, the large order group has 25 order data, cluster 2, the small order group has 361 order data and cluster 3, the medium order group has 100 order data.Keywords: data mining; order data; K-Means; sportswear manufacturing. Abstrak: Usaha Konveksi Rizky merupakan perusahaan produksi pakaian olahraga yang berpusat di Jalan Elang Lestari Kisaran. Setiap hari mereka menerima pesanan dari sekolah dan instansi yang membutuhkan pakaian olahraga. Namun Konveksi Rizky sering menghadapi tantangan terutama dalam pengelolaan persediaan bahan baku kain, pengalokasian waktu produksi dan pemrosesan pesanan yang datang dalam jumlah banyak. Untuk itu, data pesanan perlu dikelompokkan untuk mempermudah karyawan dalam mengerjakannya. Data yang akan diproses pada penelitian ini adalah data pesanan dari tahun 2022-2024. Salah satu cara untuk hal tersebut adalah dengan menerapkan teknik data mining, salah satunya metode K-Means Clustering. Tujuan penelitian ini adalah untuk memodelkan penggunaan K-Means Clustering untuk meningkatkan manajemen produksi dan pengadaan bahan baku kain di Rizky Konveksi. K-Means Clustering adalah pengelompokan sejumlah data ke dalam cluster (group) sehingga setiap dalam cluster tersebut akan berisi data yang semirip mungkin. Hasil pengelompokkan K-Means Clustering dengan 3 cluster yaitu cluster 1 kelompok pesanan banyak memiliki 25 data pesanan, cluster 2 kelompok pesanan sedikit memiliki 361 data pesanan dan cluster 3 kelompok pesanan sedang memiliki 100 data pesanan.Kata kunci: data mining; data pesanan; K-Means; konveksi.